MACRO-MICROSCOPIC FEATURES OF THE RELIEF OF THE MUCOUS MEMBRANE OF THE GASTROINTESTINAL TRACT OF WHITE RATS - Hryn, V.H. (World of Medicine and Biology, 2019)
Information about the features of the anatomical structure of the gastrointestinal tract of white rats can be gleaned from the work of many authors who are engaged in experimental modeling of various pathological conditions of the digestive system. The information available in the literature about the structural features of the white rats gastrointestinal tract needs to be checked and some clarifications. The purpose of the work was refinement and generalization of the data obtained on the macro- and microscopic structure of the gastrointestinal tract mucous membrane relief in white rats. The study was carried out on 30 white male rats. The material for the study was remote preparations of the gastrointestinal tract of white rats: the stomach, duodenum, small intestine at the site of Peyer’s patches, small intestine between Peyer’s patches and the cecum. In other cases, the gastrointestinal tract was filled with saline. Total preparations of the gastrointestinal tract were fixed in a 10% solution of neutral formalin. The cecum of the volume of proportionality is incomparably greater than that of humans. This is easily explained by the fact that in the diet of white rats products that contain vegetable fiber predominate in a significant amount. But along with this, the process of symbiotic fermentation of foodstuffs in white rats, also carried out in the proventriculus. The small intestine in white rats according to the basic morphological features is fully consistent with that of the human. It gives the full right to use it as a model for experimental reproduction of the respective localization of pathological processes.